AB0403 VALIDATION OF 2019 EULAR/ACR CLASSIFICATION CRITERIA FOR SYSTEMIC LUPUS ERYTHEMATOSUS IN A SOUTH INDIAN COHORT. (2nd June 2020) - Chalakkarayil Bhagavaldas, M.; B, H.; Balan, S.
Abstract : Background: New 2019 EULAR/ACR classification criteria for Systemic Lupus Erythematosus (SLE) has been recently published 1 . Before its widespread use in research, this criterion needs to be externally validated in other cohorts. Validation studies for the new criteria were not yet done in the Indian population. Moreover, the new 2019 EULAR/ACR classification criteria for SLE has not been validated in juvenile SLE. Objectives: To compare the real-world performance of 2019 EULAR/ACR classification criteria when applied to a known cohort of SLE cases, comprising both adult and juvenile SLE, in South Indian population. Methods: We retrospectively reviewed the electronic medical record of 30, 541 patients who visited the Rheumatology department of Amrita Institute of Medical Sciences, Kochi, a tertiary care centre in Kerala, from January 2014 to June 2019. 347 patients diagnosed with SLE by qualified and experienced rheumatologists were included in the study. 44 patients were later excluded as they were found to have an overlap syndrome. From the 30, 541 patients, another 303 age-matched patients, who attended the rheumatology department on the first week of each month, from 2014 January to 2019 June, and diagnosed with autoimmune diseases other than SLE, were selected as controls. They were selected regardless of their specific clinical or immunologic manifestations. Patients were excluded if the diagnosis was uncertain. Each patient was evaluated to see if he or she satisfied the 1997, 2012, and 2019 classification criteria, respectively. Results: Conclusion: In our cohort, the new 2019 EULAR/ACR criteria attained better sensitivity, PPV, NPV and accuracy when compared to ACR 1997 and SLICC 2012 criteria, and had almost the same specificity as compared to SLICC 2012 and ACR 1997 criteria. References: [1]Aringer M, Costenbader K, Daikh D, et al. 2019 European League against Rheumatism/American College of rheumatology classification criteria for systemic lupus erythematosus. Ann Rheum Dis2019;78:1151–9 [2]Petri M, Orbai A-M, Alarcón GS, et al. Derivation and validation of the systemic lupus international collaborating clinics classification criteria for systemic lupus erythematosus. Arthritis Rheumatism 2012;64:2677–86 [3]Hochberg MC. Updating the American College of rheumatology revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum1997;40 Disclosure of Interests: None declared